Corporate climate‐related voluntary disclosures: Does potential greenwash exist among Australian high emitters reports? - Wedari, Linda Kusumaning; Jubb, Christine; Moradi‐Motlagh, Amir (Business strategy and the environment, 2021)
This study examines the issue of greenwashing among corporate high emitters subject to government scrutiny. To do so, we investigate the relationship between the actual environmental performance, measured as carbon emissions, of companies subject to the Australian National Greenhouse Energy Reporting Act 2007 (NGER) and their climate‐related voluntary disclosures. To measure climate‐related disclosure, we construct a climate‐related disclosure index based on four prominent frameworks and score corporate report content against that Index. Using a sample of 150 companies with NGER emissions data for Years 2016 and 2017, a period that precedes the issuance of recommendations for disclosure by the Task Force on Climate‐Related Financial Disclosure (TCFD), our regression results show a disappointingly low level of climate‐related disclosure by most companies. We also find a negative relationship between climate‐related disclosure and 1‐year lagged environmental performance among companies exhibiting a year‐on‐year rise in carbon emissions. That is, our findings provide evidence of potential greenwashing by poor environmental performers, presumably to change negative perceptions by stakeholders, as predicted by socio‐political theories. In contrast, we find no evidence of greenwashing among companies experiencing a year‐on‐year decrease in emissions.